Performance of golden delicious apples grown in a semi-arid region under partial rootzone drying - Zegbe J.A.; Serna A.; Bravo A.G. (Water saving in Mediterranean agriculture and future research needs [Vol. 1], 2007)
Plant-water availability represents the main environmental limitation for arid and semiarid agro-ecosystems where water for irrigating is scarce and expensive resource for apple production. This is the case for the North part of Mexico where 70 percent (= 44 thousand hectares) of apples are grown. The objective of this research work was to determine the impact of partial rootzone drying (PRD) on the pre- and post-harvest performance of Golden Delicious apple grown in a semiarid region. Treatments were: full irrigation (FI, as control) and PRD. The 100 percent and 50 percent of the irrigation water depth (IWD) was supplied to FI and PRD, respectively. In the latter treatment, irrigation was given alternatively from the wetted side to the drying side of the root system every 8 days or when soil water content reached a threshold of soil water depletion. In general, leaf water potential appeared unaffected by treatments. Yield was the same between treatments, but water use efficiency was higher in PRD trees by 70 percent. A soil water balance pointed out that PRD saved water by ca 44 percent. Mean weight, flesh firmness, total soluble solids concentration of fruit were the same between treatments. Concentration of dry matter of fruit was higher in PRI trees than in FI trees. Fruit quality parameters were consistent after storage for 18 days (15 oC and 53 percent of relative humidity). Fruit weight loss was similar between treatments. There was a strong tendency to enhance fruit quality by PRD which deserves to be further studied in other apple cultivars for their implications for fresh-marketing and long-term storage.
Proceedings of the International Conference WASAMED Project (EU contract ICA3-CT-2002-10013), 2007/02/14-17, Valenzano (Italy)